Analisis Keterampilan Menulis Karangan Narasi Siswa Kelas V SDN Tanjung Jati 2 Tahun Ajar 2024/2025 - Ilmiarah, Firdausi Atiqah; Setyawan, Agung; Widayati, Sih (Citra Dharma Cindekia, 2024)
This research aims to analyze the narrative essay writing skills of fifth grade students at SDN Tanjung Jati 2 in the 2024/2025 academic year. Writing skills are an important aspect of language learning, especially for developing students' critical and creative thinking abilities. The research method used is descriptive qualitative, with data collection through documentation studies and interviews. The research results show that students' writing skills are generally in the sufficient and poor categories. Eleven students were able to write essays with good structure, although there were still errors in the use of punctuation and word choice. On the other hand, seven students showed poor writing skills, with some of them still having difficulty in constructing sentences cohesively, using spelling and correct punctuation. This research also reveals that students do not understand the basic rules for writing narrative essays and are rarely given writing assignments by teachers. The conclusion of this research emphasizes the importance of teacher support in familiarizing students with writing in order to improve their writing skills.